“It’s happening!” – memes as vehicle for online extremism based on an example of narratives from 4chan’s /pol/ (politically incorrect) board in the wake of Christchurch terrorist attack - Wojciechowski, Patryk (Studia Etnologiczne i Antropologiczne, 2023)
Online spaces, discussion boards, social media or open forums provide currently active generations of netizens with places to openly discuss ways in which they perceive the world, from their views on entertainment to political sympathies. Memes play an important role in that process as symbolic representations of emotions, humour and supported or opposed values. However, they may also present often inappropriate content in accessible way, hidden under the guise of irony or innocent fun. This article presents a discourse analysis conducted on a sample of 40 discussion threads posted on 4chan’s /pol/ board after the Christchurch terrorist attack. It aims to look into how through the use of memes and ironic posting such acts might be used to desensitize users to violence and extremist ideologies, while briefly covering core characteristics of memes and describing the notion of chan culture. It also touches on the matter whether such discourses, grounded in board users’ linguistic practices and the socio-cultural environment of /pol/, could be (re)producing (symbolic) violence.